Health-related quality of life in French adolescents and adults: norms for the DUKE Health Profile - Collin Jean-François; Régat Stéphanie; Gautier Arnaud; Perret-Guillaume Christine; Erpelding Marie-Line; Baumann Cédric; Guillemin Francis; Briançon Serge (BMC, 2011)
Abstract Background The continual monitoring of population health-related quality of life (HRQoL) with validated instruments helps public health agencies assess, protect, and promote population health. This study aimed to determine norms for the French adolescent and adult general population for the Duke Health Profile (DUKE) questionnaire in a large representative community sample. Methods We randomly selected 17,733 French people aged 12 to 75 years old in 2 steps, by households and individuals, from the National Health Barometer 2005, a periodic population study by the French National Institute for Prevention and Health Education. Quality of life and other data were collected by computer-assisted telephone interview. Results Normative data for the French population were analyzed by age, gender and self-reported chronic disease. Globally, function scores (best HRQoL=100) for physical, mental, social, and general health, as well as perceived health and self-esteem, were 72.3 (SEM 0.2), 74.6 (0.2), 66.8 (0.1), 71.3 (0.1), 71.3 (0.3), 76.5 (0.1), respectively. Dysfunction scores (worst HRQoL=100) for anxiety, depression, pain and disability domains were 30.9 (0.1), 27.6 (0.2), 34.3 (0.3), 3.1 (0.1), respectively. Conclusion The French norms for adolescents and adults for the DUKE could be used as a reference for other studies assessing HRQoL, for specific illnesses, in France and for international comparisons.